Towards sustainable multi-bed hospital wards: numerical evaluation of infection control, thermal comfort, and energy savings under real-world ventilation strategies - Mei Yan Chong; Hui An; Brenda Sze Peng Ang; Chew Beng Soh; Szu-Cheng Chien; Peng Cheng Wang; Simon Ching Man Yu (Energy and Buildings, 2026)

Optical properties of dissolved organic matter play pivotal roles in mediating trace metal forms in a mangrove-dominated tidal estuary - Keisuke Nakayama; Meng-Chi Hung; Chih-Yu Chiu; Sen-Lin Tang; Mei-Li Hsueh; Chin-Ching Wu; I-Hao Hung; Ya-Hsin Liu; Jeng-Wei Tsai (Marine Pollution Bulletin, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

Social-ecological memories as references for biodiversity restoration and conservation action in coastal community - Chia-Hsuan Hsu; Yu-Wen Wu; Jiefeng Kang; Hung-Kai Chiu; Mei-Ching Li; Wei-Ting Chen (Marine Pollution Bulletin, 2025)

Reducing melamine exposure and oxidative stress markers in melamine-exposed workers: A pragmatic intervention study - Chia-Fang Wu; Chih-Hong Pan; Yu-Ming Hsu; Chiung-Yu Peng; Ching-Mei Cheng; Sih-Syuan Li; Chien-Ping Huang; Ming-Tsang Wu (Journal of Hazardous Materials, 2025)

Pixel array-based urine biosensor for detection of trimethylamine N-oxide and glucose for early detection of diabetic kidney disease - Mei-Ching Yu; Chi-Jen Lo; Wei-Cheng Lin; Wei-Lun Yen; Yun-Yu Hsieh; Bing-Hong Chen; Fu-Sung Lo (Analytica Chimica Acta, 2025)

4-Anilinoquinolinylchalcone derivatives mediate antifibrotic effects through ERK/MRTF—a signaling pathway crosstalk - Padhmavathi Selvam; Chih Hua Tseng; Ching Tung Wang; Yu-Yo Sun; Yeh-Long Chen; Yu-Tse Kao; Hans-Uwe Dahms; Chih Mei Cheng (Environmental Science and Pollution Research, 2025)

Multiscale modelling and infection probability of SARS-CoV-2 transmission in a typical lecture theatre - Mei Yan Chong; Hui An; Peng Cheng Wang; Chew Beng Soh; Szu-Cheng Chien; Edward Reuben Roch; Jun Jie Koh; Simon Ching Man Yu (Building and Environment, 2025)

Using Gaussian Mixture Model Clustering for the Automated Segmentation of Cerebral Arteriovenous Malformations in Magnetic Resonance Images - Ting-Yu Lin; Cheng‑Chia Lee; Yu-Wei Chen; Hsiu-Mei Wu; Ching-Jen Chen; Huai-Che Yang; Syu-Jyun Peng (Journal of Medical and Biological Engineering, 2025)

Rational design of stable Cu and AuCu nanoparticles for investigations of size-enhanced SERS applications - Kuan-Wen Liu; Pei-Yu Sie; Jing-Yin Huang; Hsi-Ying Chen; Yi-Lun Chen; Yu-Ching Lin; Mei-Yi Liao (Analytica Chimica Acta, 2024)

The Association of Bisphenol A and Parabens Exposure and Oxidative Stress in Attention-Deficit/Hyperactivity Disorder in Children and Adolescents - Boopathi Subramani; Chia-Huang Chang; Ting-Yu Fang; Ching-Jung Yu; Jung-Chieh Du; Hsien-Chih Chiou; Jia-Woei Hou; Winnie Yang; Hsin-Chang Chen; Ying-Sheue Chen; Betau Hwang; Mei-Lien Chen (Exposure and Health, 2024)

Hyperlactatemia is associated with increased risks of long-term mortality and major adverse cardiovascular events in sepsis survivors - Shu-Yu Ou; Yi-Jung Lee; Yu-Mei Chou; Gwo-Ching Sun; Yuan-Yi Chia (Infectious Diseases, 2023)

Phylogenetic divergence associated with climate oscillations and topology illustrates the dispersal history of Formosan sambar deer (Rusa unicolor swinhoii) in Taiwan - Kuan-Yi Li; Chen Hsiao; Shih-Ching Yen; Chien-Yi Hung; You-Zhu Lin; Sheng-Wun Jheng; Pei-Ju Yu; Mei-Hsiu Hwang; Guo-Jing Weng; Ku-Lin Chen; Shu-Fen Lin; Shih-Wei Chang; et al. (Mammal Research, 2023)
The island of Taiwan represents an ideal context for studying the effects of climatic oscillations and topographic variation on large herbivores due to its varied tropical to sub-tropical climate zones at different elevational ranges. We explored the phylogenetics of Formosan sambar deer ( Rusa unicolor swinhoii ) using the control region of the mitochondrial genome. We detected 18 haplotypes among 454 sequences across the island and grouped them into six regions based on SAMOVA, with 68.78% variance among regions. A Bayesian phylogenetic dendrogram revealed two spatially segregated genetic clades. Neutrality tests and Bayesian skyline plots uncovered different demographic expansion histories for the two clades. We further tested divergence times and chronology to propose potential phylogenetic scenarios, which were examined using approximate Bayesian computation. Finally, we present a credible hypothesis for a glacial refugium in the northern part of the Central Mountain Range. Subsequent secondary contact between the two clades during interglacial periods has led to the extant genetic structure of Formosan sambar deer.

Identification of serum metabolic signatures of environmental-leveled phthalate in the Taiwanese child population using NMR-based metabolomics - Sheng-Han Lee; Zhi-Yi Du; Wei-Chen Tseng; Wan-Yu Lin; Mei-Huei Chen; Ching-Chun Lin; Hao-Jan Liang; Hui-Ju Wen; Yue-Leon Guo; Pau-Chung Chen; Ching-Yu Lin (Environmental Pollution, 2023)

Doping engineering of carrier transporting layers for ambient-air-stable lead-free rudorffite solar cells prepared by thermal-assisted doctor blade coating - Kai-Chi Hsiao; Yen-Fu Yu; Ching-Mei Ho; Meng-Huan Jao; Yu-Hsiang Chang; Shih-Hsuan Chen; Yin-Hsuan Chang; Wei-Fang Su; Kun-Mu Lee; Ming-Chung Wu (Chemical Engineering Journal, 2023)

Phenylpropanoids and lignoids from the whole plant of Vaccinium emarginatum and their cytotoxicity against prostate cancer cells - Ping-Chen Tu; Yu-Chia Liang; Ming-Ching Kao; Louis Kuoping Chao; Mei-Hwei Tseng; Te-Ling Lu; Ping-Jyun Sung; Yueh-Hsiung Kuo (Natural Product Research, 2021)

Molecular survey of selected viral pathogens in wild leopard cats (Prionailurus bengalensis) in Taiwan with an emphasis on the spatial and temporal dynamics of carnivore protoparvovirus 1 - Chen-Chih Chen; Ai-Mei Chang; Wan-Jhen Chen; Po-Jen Chang; Yu-Ching Lai; Hsu-Hsun Lee (Archives of Virology, 2021)

Targeting Inflammation, PHA-767491 Shows a Broad Spectrum in Protein Aggregation Diseases - Yu-Han Chung; Chia-Wei Lin; Hsin-Yu Huang; Shu-Ling Chen; Hei-Jen Huang; Ying-Chieh Sun; Guan-Chiun Lee; Guey-Jen Lee-Chen; Ya-Ching Chang; Hsiu Mei Hsieh-Li (Journal of Molecular Neuroscience, 2020)

Population Structure of the World Vegetable Center Mungbean Mini Core Collection and Genome-Wide Association Mapping of Loci Associated with Variation of Seed Coat Luster - Caleb Manamik Breria; Ching Hsiang Hsieh; Jo-Yi Yen; Ramakrishnan Nair; Chen-Yu Lin; Shu-Mei Huang; Thomas J. Noble; Roland Schafleitner (Tropical Plant Biology, 2020)

Adenosine Augmentation Evoked by an ENT1 Inhibitor Improves Memory Impairment and Neuronal Plasticity in the APP/PS1 Mouse Model of Alzheimer’s Disease - Chia-Chia Lee; Ching-Pang Chang; Chun-Jung Lin; Hsing-Lin Lai; Yu-Han Kao; Sin-Jhong Cheng; Hui-Mei Chen; Yu-Ping Liao; Emilie Faivre; Luc Buée; David Blum; Jim-Min Fang; et al. (Molecular Neurobiology, 2018)

Web-Based Experience Sharing Platform on Medical Device Incidents for Clinical Engineers in Hospitals - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Yu-Wen Huang; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2018)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Identification and quantification of Cu-chlorophyll adulteration of edible oils - Mingchih Fang; Chia-Fen Tsai; Guan-Yan Wu; Su-Hsiang Tseng; Hwei-Fang Cheng; Ching-Hao Kuo; Che-Lun Hsu; Ya-Min Kao; Daniel Yang-Chih Shih; Yu-Mei Chiang (Food Additives & Contaminants Part B-Surveillance, 2015)

Methodology of disaster risk assessment for debris flows in a river basin - Ing-Jia Chiou; Ching-Ho Chen; Wei-Lin Liu; Shiao-Mei Huang; Yu-Min Chang (Stochastic Environmental Research and Risk Assessment, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Association Study Between Macrophage Migration Inhibitory Factor-173 Polymorphism and Acute Myeloid Leukemia in Taiwan - Latha Ramireddy; Chien-Yu Lin; Su-Ching Liu; Wan-Yu Lo; Rouh-Mei Hu; Yi-Chin Peng; Ching-Tien Peng (Cell Biochemistry and Biophysics, 2014)

Diverse chromosome complements in the functional gametes of interspecific hybrids of MT- and A-karyotype Lycoris spp. - Yu-Chu Chang; Chou-Tou Shii; Yi-Ching Lee; Mei-Chu Chung (Plant Systematics and Evolution, 2013)

Isolation of marine bacteria with antimicrobial activities from cultured and field-collected soft corals - Yu-Hsin Chen; Jimmy Kuo; Ping-Jung Sung; Yu-Chia Chang; Mei-Chin Lu; Tit-Yee Wong; Jong-Kang Liu; Ching-Feng Weng; Wen-Hung Twan; Fu-Wen Kuo (World Journal of Microbiology and Biotechnology, 2012)

Development of transgenic watermelon resistant to Cucumber mosaic virus and Watermelon mosaic virus by using a single chimeric transgene construct - Ching-Yi Lin; Hsin-Mei Ku; Yi-Hua Chiang; Hsiu-Yin Ho; Tsong-Ann Yu; Fuh-Jyh Jan (Transgenic Research, 2012)

Investigations into the Correlation Properties of Membrane Electroporation-Induced Inward Currents: Prediction of Pore Formation - Sheng-Nan Wu; Chia-Chen Yeh; Pei-Yu Wu; Hsien-Ching Huang; Mei-Ling Tsai (Cell Biochemistry and Biophysics, 2012)

Down-Regulation of Tumor-Associated NADH Oxidase, tNOX (ENOX2), Enhances Capsaicin-Induced Inhibition of Gastric Cancer Cell Growth - His-Ming Wang; Show-Mei Chuang; Yu-Ching Su; Yi-Hui Li; Pin Ju Chueh (Cell Biochemistry and Biophysics, 2011)

Generation of transgenic watermelon resistant to Zucchini yellow mosaic virus and Papaya ringspot virus type W - Tsong-Ann Yu; Chu-Hui Chiang; Hui-Wen Wu; Chin-Mei Li; Ching-Fu Yang; Jun-Han Chen; Yu-Wen Chen; Shyi-Dong Yeh (Plant Cell Reports, 2011)

Establishment of an arabinose-inducible system in Stenotrophomonas maltophilia - Yi-Wei Huang; Rouh-Mei Hu; Yu-Ting Chiang; Tsao-Chuen Chung; Tung-Ching Chung; Tsuey-Ching Yang (Folia Microbiologica, 2011)

Association between human papillomavirus and adenocarcinoma of rectum and recto-sigmoid junction: a cohort study of 10,612 women in Taiwan - Li-Chung Chuang; Hui-Chi Chen; San-Lin You; Ching-Yu Lin; Mei-Hung Pan; Yi-Chun Chou; Chang-Yao Hsieh; Chien-Jen Chen (Cancer Causes & Control, 2010)

Constitutive expression of a fungal glucose oxidase gene in transgenic tobacco confers chilling tolerance through the activation of antioxidative defence system - Subbiyan Maruthasalam; Yi Lun Liu; Ching Mei Sun; Pei Ying Chen; Chih Wen Yu; Pei Fang Lee; Chin Ho Lin (Plant Cell Reports, 2010)

Involvement of the residues of GSKIP, AxinGID, and FRATtide in their binding with GSK3β to unravel a novel C-terminal scaffold-binding region - Shen-Long Howng; Chi-Ching Hwang; Chia-Yi Hsu; Meng-Yu Hsu; Chun-Yen Teng; Chia-Hua Chou; Mei-Feng Lee; Chia-Hung Wu; Shean-Jaw Chiou; Ann-Shung Lieu; Joon-Khim Loh; Chia-Ning Yang; et al. (Molecular and Cellular Biochemistry, 2010)

Early-life or lifetime sun exposure, sun reaction, and the risk of squamous cell carcinoma in an Asian population - Yen-Ching Chen; David C. Christiani; Huey-Jen Jenny Su; Yu-Mei Hsueh; Thomas J. Smith; Louise M. Ryan; Sheau-Chiou Chao; Julia Yu-Yun Lee; Yue-Liang Leon Guo (Cancer Causes & Control, 2010)

A novel mutation in the connexin 29 gene may contribute to nonsyndromic hearing loss - Hui-Mei Hong; Jiann-Jou Yang; Ching-Chyuan Su; Juan-Yu Chang; Tung-Cheng Li; Shuan-Yow Li (Human Genetics, 2010)

Numerical investigation and identification of susceptible sites of atherosclerotic lesion formation in a complete coronary artery bypass model - Jun-Mei Zhang; Leok Poh Chua; Dhanjoo N. Ghista; Simon Ching Man Yu; Yong Seng Tan (Medical & Biological Engineering & Computing, 2008)

Development of a molecular marker for a bruchid (Callosobruchus chinensis L.) resistance gene in mungbean - Huei-Mei Chen; Chien-An Liu; C. George Kuo; Ching-Mei Chien; Horng-Chi Sun; Chung-Chu Huang; Yu-Chung Lin; Hsin-Mei Ku (Euphytica, 2007)

Production of high-content galacto-oligosaccharide by enzyme catalysis and fermentation with Kluyveromyces marxianus - Chao-Chun Cheng; Mei-Ching Yu; Tzu-Chien Cheng; Dey-Chyi Sheu; Kow-Jen Duan; Wei-Lun Tai (Biotechnology Letters, 2006)

Production of High-content Galacto-oligosaccharide by Enzyme Catalysis and Fermentation with Kluyveromyces marxianus - Chao-Chun Cheng; Mei-Ching Yu; Tzu-Chien Cheng; Dey-Chyi Sheu; Kow-Jen Duan; Wei-Lun Tai (Biotechnology Letters, 2006)

Transgenic tomato plants expressing the Arabidopsis NPR1 gene display enhanced resistance to a spectrum of fungal and bacterial diseases - Wan-Chi Lin; Ching-Fang Lu; Jia-Wei Wu; Ming-Lung Cheng; Yu-Mei Lin; Ning-Sun Yang; Lowell Black; Sylvia K. Green; Jaw-Fen Wang; Chiu-Ping Cheng (Transgenic Research, 2004)

Detection of cefotaxime-resistant CTX-M-3 in clinical isolates ofSerratia marcescens - Mei-Fen Tsou; Wen-Liang Yu; Siu Wan Hung; Chizh-Ju Chi; Chieh-Ju; Ssu Ching Chen; Lii-Tzu Wu (Folia Microbiologica, 2004)

Arsenic methylation and bladder cancer risk in Taiwan - Yen-Ching Chen; Huey-Jen Jenny Su; Yu-Liang Leon Guo; Yu-Mei Hsueh; Thomas J. Smith; Louise M. Ryan; Meei-Shyuan Lee; David C. Christiani (Cancer Causes & Control, 2003)